The Effectiveness Of The Protective Barrier Of The Skin Against Medical Adhesive Related Skin Injury (Marsi) In Children Treated In Pediatric Intensive Care Units : Systematic Review - Mutifa, Juanda; Nani Nurhaeni; Dessie Wanda (STIKep PPNI Jawa Barat, 2022)
Aims: Providing medical equipment intervention increases the risk of MARSI in newborns with laceration and traumatic wounds in the subcutaneous tissue of the skin. The application of an adhesive or a skin barrier is one technique to lower the risk of MARSI. Nonetheless, past research has yielded mixed results in terms of its usefulness in reducing the risk of MARSI. Purpose: This study is to conduct a literature evaluation on the effectiveness of using a skin barrier to reduce the occurrence of MARSI. Methods: A systematic review of four databases was conducted, including Scopus, EBSCOhost, SAGE, and Wiley. A total of 8 publications were reviewed utilizing inclusion and exclusion criteria with a total end of article review. Results: The application of adhesive efficiently and considerably reduces the risk of MARSI, according to 5 of 8 articles. Conclusion: It is recommended that adhesive be used in an integrated manner on a regular basis to prevent the incidence of MARSI in babies.